Moriska Paviljongen - Konceptmodell - (:unkn) unknown (Chalmers tekniska högskola // Institutionen för arkitektur och samhällsbyggnadsteknik, 2025)
Moriska Paviljongen, located in Malmö, Sweden, was originally built as a palace of entertainment for the peoples movement. It has over the years been extended multiple times but the function remains similar, hosting night clubs and concerts. The building has a neo-moorish design, popular in europe at the time, and features horseshoe arches and onion domes.
Moriska Paviljongen - Concept model
Keywords: moorish; morisk stil; malmö; horseshoe arch; onion dome; folkets park